2003
DOI: 10.1002/ceat.200390008
|View full text |Cite
|
Sign up to set email alerts
|

Local Velocity and Concentration of the Single Components in Water/Oil Mixtures Monitored by Means of MRI Flow Experiments in Steady Tube Flow

Abstract: In this paper the spatially resolved determination of velocities in two-phase systems consisting of water and oil by means of nuclear magnetic resonance (NMR) imaging (MRI) techniques is described and applied to steady tube flows with regard to the total flow rate. As MRI offers the possibility to study the flow of multiphase materials spatially resolved with various forms of contrast, even optically opaque water/oil mixtures can be studied in the interior of the material. Besides snapshot images of the actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This chemical shift is quite small (about 4-4.5 ppm relative difference, whenever carbon or silicon oils are used). Nevertheless this shift can be accurately observed provided that B o inhomogeneities across the sample have a much smaller amplitude than 4.5ppm of the mean B o value (e.g., see spectrum by Götz and Zick [31]). Indeed, the precession frequency is also proportional to local B o intensity, and one should avoid confusion between the original chemical shift and any spurious one originating from field heterogeneities.…”
Section: Concentration Measurementsmentioning
confidence: 95%
See 1 more Smart Citation
“…This chemical shift is quite small (about 4-4.5 ppm relative difference, whenever carbon or silicon oils are used). Nevertheless this shift can be accurately observed provided that B o inhomogeneities across the sample have a much smaller amplitude than 4.5ppm of the mean B o value (e.g., see spectrum by Götz and Zick [31]). Indeed, the precession frequency is also proportional to local B o intensity, and one should avoid confusion between the original chemical shift and any spurious one originating from field heterogeneities.…”
Section: Concentration Measurementsmentioning
confidence: 95%
“…Quite early results deal with the use of chemical shift imaging (CSI) for a quantitative assessment of oil/fat content in food emulsions [32], or the separation of oil and water components of an emulsion during a filtration process [33]. More recently, Götz and Zick [31] and Hollingsworth and Johns [17] managed to carry out quite well resolved local measurements of water/oil concentrations and/or velocities in model suspensions flowing through a pipe in a laminar regime. Unfortunately, the chemical shift contrast can hardly be transposed in the case of a Couette cell.…”
Section: Concentration Measurementsmentioning
confidence: 99%
“…these applications is that the distribution of the phases in the flow has a great impact on the flow properties (for instance, the pressure drop), but the fluid distribution in general is not known. Although in principle MRI is a powerful tool to use to access both velocity and concentration profiles in a flowing system, few MRI experiments on multiphase flow exist (Götz & Zick 2003, Le Gall et al 2001, Muller et al 2007). …”
Section: Mri Velocimetry: Trends In Methodologymentioning
confidence: 99%
“…Later works combining NMR velocimetry and deuterium NMR spectroscopy have shown that birefringence bands do not necessarily correspond to shear bands [61,62]. Finally, more recently, fast NMR velocimetry allowed the authors to resolve temporal fluctuations of the flow field [83,122,123] Since the early work by Callaghan et al, NMR velocimetry has been used in a growing number of complex fluids to investigate shear banding or shear localization including emulsions [67], colloidal systems [82,196], wet granular materials [91], cement pastes [98], and other soft glassy materials studied by Coussot et al [28,44,168,170].…”
Section: Characterizing the Velocity Field Of Shear-banded Flowsmentioning
confidence: 99%